2013
DOI: 10.1214/13-aos1096
|View full text |Cite
|
Sign up to set email alerts
|

A lasso for hierarchical interactions

Abstract: We add a set of convex constraints to the lasso to produce sparse interaction models that honor the hierarchy restriction that an interaction only be included in a model if one or both variables are marginally important. We give a precise characterization of the effect of this hierarchy constraint, prove that hierarchy holds with probability one and derive an unbiased estimate for the degrees of freedom of our estimator. A bound on this estimate reveals the amount of fitting “saved” by the hierarchy constraint… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
645
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 418 publications
(650 citation statements)
references
References 41 publications
2
645
3
Order By: Relevance
“…A comparative analysis is then done with the generalised additive models (GAMs) which are used as benchmark models. In this study, we discuss an application of pairwise hierarchical interactions discussed in Bien et al [24] and Laurinec [25] who showed that the inclusion of interactions improves forecast accuracy.…”
Section: Contextmentioning
confidence: 99%
“…A comparative analysis is then done with the generalised additive models (GAMs) which are used as benchmark models. In this study, we discuss an application of pairwise hierarchical interactions discussed in Bien et al [24] and Laurinec [25] who showed that the inclusion of interactions improves forecast accuracy.…”
Section: Contextmentioning
confidence: 99%
“…Moreover, it can be helpful to integrate additional assumptions concerning the model structure to guide the learning process in the spirit of [1,10]. This can be achieved by modifying the Lasso penalization in various ways.…”
Section: Discussionmentioning
confidence: 99%
“…However, they only interactions defined using the and operator. To allow more types of Boolean operations, the works in [1] and [10] incorporate extra information such as the structure of coefficients to guide the learning process. However, these methods need expert knowledge that is not always available.…”
Section: Related Workmentioning
confidence: 99%
“…By expressing Equation 10 Electricity, including temperature data used in this study, is discussed in the next sub-sections. The variables used were later selected using the shrinkage method Lasso via hierarchical pairwise interactions discussed in Bien et al (2013), meaning that variables included in the interactions, i.e., cross-effects, will also be included in the main effects.…”
Section: The Generalised Additive-tensor Product Interactions Model Wmentioning
confidence: 99%